Geochemical Fingerprint Distortion and Elemental Decoupling of Heavy Metals in Livestock Manure Driven by Farming Intensification - Qiu Cheng; Yi Jijun; Gan Jinyu; Zhang Jun; Ling Chaosheng; Bai Yang; Du Qiuxiang; Li Qianglin; Wang Liting; Wang Mingxi; Fan Shoubo (International Journal of Environmental Research, 2026)

Transesterification for electronic-grade propylene glycol methyl ether acetate: Catalysis, deactivation & purification - Kaiqi Du; Guangpeng Chen; Hao Pan; Liting Fan; Huiping Xu; Wenqiu Su; Shaolong Wan; Wenjing Hong (Chemical Engineering Journal, 2026)

Harnessing mycelium-based morphology of filamentous fungi in food biomanufacturing: Integrated advances, challenges, and future perspectives - Mengmeng Xu; Song Ming; Jiahao Cui; Yuxi Guo; Liting Zhao; Lei Chen; Guiyang Shi; Daming Fan; Zhongyang Ding (Trends in Food Science & Technology, 2026)

Quantifying the decoupling of pollution magnitude and geochemical signatures in livestock manure: a novel geometric fingerprint approach - Qiu Cheng; Yi Jijun; Fan Shoubo; Du Qiuxiang; Li Qianglin; Wang Liting; Liang Qingling; Zheng Guihua; Xiong Ping (Environmental Monitoring and Assessment, 2026)

Experimental Study on Suppression and Mechanism of Sloshing Impact Pressure by Vertical Slat Screens Under Broadband Horizontal and Vertical Excitation - Liting Yu; Xiaoqian Luo; Jingcheng Lin; Jie Fan; Heng Jin (Journal of Marine Science and Engineering, 2026)
Sloshing-induced impact pressure is a key damage factor for marine liquid tanks. While research aimed at overcoming screen failure in sloshing suppression under high-frequency excitation has focused on wave height, the dataset of impact pressure remains lacking. Moreover, the pattern of pressure suppression under broadband excitation remains unclear. The primary contribution of this work is the first experimental dataset of impact pressure with vertical slat screens under broadband horizontal and vertical excitation. Second, it reveals pressure suppression patterns by screens across varying excitation frequencies and screen numbers. The results demonstrate that vertical slat screens can effectively suppress pressure. First, screen position matters more than number, proving that suppression is dominated by modal disturbance. Second, wave-height suppression does not reliably represent pressure suppression. Pressure suppression is systematically weaker. An exception occurs under vertical excitation, where pressure suppression can be stronger even when wave-height suppression fails. The results highlight the suppression mechanism dominated by modal disturbance and the instability inherent to parametric sloshing. Wave height, reflecting global potential energy, is effectively suppressed by modal disturbance. Pressure, originating from local kinetic energy, can be effectively suppressed by both modal disturbance and vortex dissipation.

The Reorganization of Cerebellar Functional Network Topology in Post-stroke Aphasia: A Resting-State fMRI Study - Liting Chen; Zhenye Luo; Wenfeng Mai; Xiaoling Wu; Xiaole Fan; Lifeng Li; Yongqiang Shu; Xiaoyun Chen; Qun Fang; Hong Wang; Yanhong Dai; Shuixing Zhang (Molecular Neurobiology, 2026)

Effects of Soil Components on Microplastics Transport and Retention in Natural Soils: Various Microplastics Types and Sizes - Weiya Fan; Shunan Dong; Xiyu Chen; Xiaoting Su; Qianhui Yu; Liting Sheng (Water, Air, & Soil Pollution, 2025)

Loading palladium clusters in porous organic cages for simultaneously enhancing H2 permeability and H2/CH4 selectivity of molecularly mixed composite membranes - Jia Pang; Haoyu Xu; Lu Qiao; Yao Wang; Liting Yu; Hongbin Wang; Caiyan Zhang; Hu Chang; Lili Fan; Rongming Wang; Zixi Kang; Daofeng Sun (Chemical Engineering Journal, 2025)

Synthesis of value-added uridine 5'-diphosphate-glucose from sucrose applying an engineered sucrose synthase counteracts the activity-stability trade-off - Liting Zhao; Zhongbao Ma; Linpei Zhang; Yu Shen; Lei Chen; Youran Li; Sha Xu; Guiyang Shi; Daming Fan; Zhongyang Ding (Food Chemistry, 2025)

Establishment and validation of a real-time fluorescent PCR freeze-dried type assay for 11 sheep and goats pathogens - Liting Ke; Guangzheng Hou; Pengcheng Cao; Yanlei Ding; Changxu Zhao; Fei Wang; Yingqiu Liu; Yunpeng Fan; Qiqi Liu (The Veterinary Journal, 2024)

Three-Dose Antifungal Treatment Improves the Efficacy for Severe Vulvovaginal Candidiasis - Zhansong Xiao; Yiheng Liang; Xiaowei Zhang; Yuxia Zhu; Liting Huang; Shangrong Fan (Mycopathologia, 2024)

Cotransport of 6PPD-Q and pristine/aged microplastics in porous media: An insight based on transport forms and mechanisms - Qianhui Yu; Shunan Dong; Liting Sheng; Xiaoting Su; Lei Wang; Weiya Fan; Yulu Yu (Water Research, 2024)

Study on the planning and scheduling strategies of the hydrogen supply network for road transportation in deep decarbonization scenarios - Qifen Li; Liting Zhang; Zhenkun Qin; Jiejie Guo; Yongwen Yang; Hongbo Ren; Longfei Fan; Nengling Tai (Sustainable Cities and Society, 2024)

The structure correspondence hypothesis predicts how word and sentence in language correlate with term and principle in mathematics - Jiaxin Cui; Liting Lv; Fan Yang; Lelei Wang; Jiarui Li; Zhanling Cui; Xinlin Zhou (Cognitive Processing, 2024)

Research progress on the extraction technology and activity study of Epimedium polysaccharides - Liting Ke; Xueqin Duan; Jing Cui; Xiaoping Song; Wuren Ma; Weimin Zhang; Yingqiu Liu; Yunpeng Fan (Carbohydrate Polymers, 2023)

Graphene quantum dots disturbed the energy homeostasis by influencing lipid metabolism of macrophages - Yan Shao; Xiaoyang Wang; Liting Wang; Youying Huang; Quanfang Wei; Wei Sun; Xiaodan Lai; Fan Yang; Fei Li; Yi Huang (Toxicology, 2023)

Sequence identification and expression profile of seven Dermacentor marginatus glutathione S-transferase genes - Huercha; Ying Ma; Yunwei Hao; Min Li; Zhengxiang Hu; Ruiqi Song; Liting Wei; Shilong Fan; Songqin Chen; Xinli Fan; Xuejie Zhai; Qingyong Guo; et al. (Experimental and Applied Acarology, 2020)

First isolation of reticuloendotheliosis virus from mallards in China - Lili Jiang; Xiaoyun Deng; Yulong Gao; Kai Li; Hongliang Chai; Zhaobin Fan; Xiangang Ren; Qi Wang; Lizhou Zhang; Bingling Yun; Chunhong Yin; Yuming Chen; et al. (Archives of Virology, 2014)

Basic and Clinical Research on the Therapeutic Effect of Intervention in Primary Liver Cancer by Targeted Intra-Arterial Verapamil Infusion - Fan Pingsheng; Zhang Tengyue; Huang Qiang; Wei Qiang; Sun Xin; Qian Liting (Cell Biochemistry and Biophysics, 2012)

Post-TACE Combination Therapy of Heparin and Octreotide Results in Decreased Tumor Metastasis in Extrahepatic Tumorigenesis - Weidong Jia; Kehai Feng; Pingsheng Fan; Gaofei Fan; Shoumei Yang; Tengyue Zhang; Qiang Wei; Liting Qian (Cell Biochemistry and Biophysics, 2012)

Clinical Evaluation of Targeted Arterial Infusion of Verapamil in the Interventional Chemotherapy of Primary Hepatocellular Carcinoma - Jin Huang; Qiaohong Duan; Pingsheng Fan; Chushu Ji; Yuying Lv; Xinmin Lin; Liting Qian; Xiukun Yu (Cell Biochemistry and Biophysics, 2011)